THE EFFECTIVENESS OF TEACHING WRITING BY USING PADLET AS THE MEDIA - Ismawardani, Betty Mahardica; Sulistyanto, Irwan (Jurnal Pendidikan Bahasa Inggris Proficiency, 2019)
Using Padlet as media is one of the ways to teach writing. Using Padlet as media help students make the students more excited in writing. The main purpose of the study is to examine the effectiveness of using Padlet as media on students’ writing score of the tenth grade IIS-1. Quantitative was selected as a research approach, whereas the research design used was Quasi Experimental by using posttest-only design. This research used two classes which became experimental and control class. The experimental class was taught writing by using Padlet as media, while the control class was taught without any media. To collect the data, post writing tests in experimental and control group were administered. Data were analyzed by using t-test. The findings indicated that score of the experimental class higher than the control class. Thus, it can be concluded that using Padlet as media in teaching writing is effective.